METHODS FOR IMPROVING STUDENTS' LOGICAL THINKING IN NATURE SCIENCE TEACHING BY USING VARIOUS TASKS - Boychayeva Sharifa Saidkulovna (Bright Mind Publishing, 2025)
The purpose and application of logical tasks in the study of natural science textbooks in elementary school classes are discussed in this article.
Keywords: Task, capacity, natural, thinking, and outcome.